MMP-12 and Periodontitis: Unraveling the Molecular Pathways of Periodontal Tissue Destruction - Lin B; Fan Y; Yang X; Pathak JL; Zhong M (Dove Medical Press, 2024)
Bingpeng Lin,1,2,* Yufei Fan,2,* Xuechao Yang,2 Janak L Pathak,2 Mei Zhong3 1Department of Orthodontics, School and Hospital of Stomatology, Guangzhou Medical University, Guangzhou, 510180, People's Republic of China; 2Guangdong Engineering Research Center of Oral Restoration and Reconstruction, Guangzhou Key Laboratory of Basic and Applied Research of Oral Regenerative Medicine, Affiliated Stomatology Hospital of Guangzhou Medical University, Guangzhou, 510182, People's Republic of China; 3Department of Prosthodontics, School and Hospital of Stomatology, Guangzhou Medical University, Guangzhou, 510180, People's Republic of China*These authors contributed equally to this workCorrespondence: Janak L Pathak; Mei Zhong, Email J.pathak@gzhmu.edu.cn; 2016686043@gzhmu.edu.cnAbstract: Periodontal disease is a common disorder affecting a wide range of people and has a high prevalence globally. Periodontitis comprises a series of inflammatory conditions affecting periodontal support tissue, which could ultimately lead to tooth loss and reduce life quality and add to the financial burden of society. Matrix metalloproteinase-12 (MMP-12) is an elastase that is produced mostly by macrophages and could degrade a wide spectrum of extracellular matrix (ECM) and also contribute to several systematic pathological conditions. Recently, researchers have reported higher expression of MMP-12 in chronic periodontitis patients. However, there are few reports on the role of MMP-12 in periodontitis pathogenicity, and the interaction between MMP-12, periodontal pathogens, and periodontal tissues remains unclear. In this review, we introduce the potentially unique role of MMP-12 in the context of periodontal inflammation earlier, summarize the possible effects of MMP-12 on the pathological process of periodontitis and the interaction of host response under the challenge of various inflammatory factors, and provide possible diagnostic and therapeutic strategies targeting MMP-12 for the management of periodontitis. Future research and policies should focus on and implement effective chairside testing methods to reduce the prevalence of periodontal diseases.Keywords: matrix metalloproteinase-12, periodontitis, dysbiosis, epithelial barrier, immunity, osteoimmunology